Aerosol properties over the Indo-Gangetic Plain: A mesoscale perspective from the TIGERZ experiment ... - Giles, David M.; Holben, Brent N.; Tripathi, Sachchida N.; Eck, Thomas; Newcomb, W. Wayne; Slutsker, Ilya; Dickerson, Russell R.; Thompson, Anne M.; Mattoo, Shana; Wang, Sheng-Hsiang; Singh, Remesh P.; Sinyuk, Aliaksandr; et al. (AGU, 2011)
High aerosol loading over the northern Indian subcontinent can result in poor air quality leading to human health consequences and climate perturbations. The international 2008 TIGERZ experiment intensive operational period (IOP) was conducted in the Indo-Gangetic Plain (IGP) around the industrial city of Kanpur (26.51°N, 80.23°E), India, during the premonsoon (April–June). Aerosol Robotic Network (AERONET) Sun photometers performed frequent measurements of aerosol properties at temporary sites distributed within an area covering ?50 km2 around Kanpur to characterize pollution and dust in a region where complex aerosol mixtures and semi-bright surface effects complicate satellite retrieval algorithms. TIGERZ IOP Sun photometers quantified aerosol optical depth (AOD) increases up to ?0.10 within and downwind of the city, with urban emissions accounting for ?10–20% of the IGP aerosol loading on deployment days. TIGERZ IOP area-averaged volume size distribution and single scattering albedo retrievals indicated ...